A randomized comparison of once weekly epoetin alfa to extended schedule epoetin or darbepoetin in chemotherapy‐associated anemia. Issue 10 (14th August 2015) - Steensma, David P.; Dakhil, Shaker R.; Novotny, Paul J.; Sloan, Jeff A.; Johnson, David B.; Anderson, Daniel M.; Mattar, Bassam I.; Moore, Dennis F.; Nikcevich, Daniel; Loprinzi, Charles L.
<x xml:space="preserve">Abstract</x> Erythropoiesis‐stimulating agents (ESAs) epoetin alfa (EA) and darbepoetin alfa (DA) increase hemoglobin (Hb) levels and reduce red blood cell (RBC) transfusion requirements in patients with cancer chemotherapy‐associated anemia (CAA). Extended‐interval ESA dosing (administration less than once weekly) is common with DA, but previous studies suggested that EA might also be administered less often than weekly. In this multicenter prospective trial, 239 CAA patients with Hb <10.5 g/dL were randomized to receive EA 40, 000 U subcutaneously once weekly ("40K" arm), EA 80, 000 U every 3 weeks ("80K"), EA 120, 000 U every 3 weeks ("120K" arm), or DA 500 mcg every 3 weeks ("DA"), for 15 weeks. The primary endpoint was the proportion of patients achieving Hb ≥ 11.5 g/dL or increment of Hb > 2.0 g/dL from baseline without transfusion. Secondary endpoints included transfusion requirements, adverse events (AEs), and patient‐reported outcomes (PROs). There were no significant differences between treatment arms in the proportion of patients achieving Hb response (68.9% for 40K, 61.7% for 80K, 65.5% for 120K, and 66.7% for DA; P > 0.41 for all comparisons) or requiring RBC transfusion, but the median Hb increment from baseline was higher in the 40K and DA arms compared to the two extended dosing EA arms, and Hb response was achieved soonest in the weekly EA arm. There were no differences in PROs or AEs. The FDA‐approved schedules tested—weekly EA 40, 000 U, and every 3 week DA 500 mcg—are reasonable standards for CAA therapy. Am. J. Hematol. 90:877–881, 2015. © 2015 Wiley Periodicals, Inc.